UNIT 17.15 Diagnosis of Lysosomal Storage Disorders: Gaucher Disease. (14th July 2014) - Johnson, Britt A.; Dajnoki, Angela; Bodamer, Olaf
Abstract: Gaucher Disease (GD) is a progressive lysosomal storage disorder caused by deficiency of glucocerebrosidase (GBA). The clinical phenotype follows a spectrum ranging from severe early‐onset to milder late‐onset disease. The absence of neurological involvement defines GD type I, whereas neuronopathic features define GD type II and III. Early diagnosis may be important for timely initiation of enzyme replacement therapy to prevent disease complications, although the enzyme does not cross the blood brain barrier. Diagnosis of GD can be readily achieved by analysis of GBA in leukocytes, fibroblasts, and/or dried blood spots using fluorometric, microfluidic or mass spectrometry‐based assays. Low GBA activities are typically confirmed through molecular analysis of the GBA gene. GBA analysis in dried blood spots may be attractive for high‐throughput screening of at‐risk individuals and/or newborn infants. The method detailed in this unit is based on GBA analysis by tandem mass spectrometry following incubation of dried blood spots with the GBA‐specific substrate D ‐glucosyl‐β1‐1′‐N‐dodecanoyl‐D ‐erythro‐sphingosine [C12‐glucocerebroside (C36 H69 NO8 )] and internal standard N‐myristoyl‐D ‐erythro‐sphingosine [C14‐ceramide (C32 H63 NO3 )]. GBA activities in more than 2, 000 newborn infants showed a mean of 22.0 ± 13.8 μmol/hr/liter (median: 19.9 μmol/hr/liter; 95% CI: 21.41‐22.59 μmol/hr/liter). GBA activities in an adult population (n >1, 200) showed generally lower enzyme activities than newborns, with a mean of 9.87 ± 9.35 μmol/hr/liter (median: 8.06 μmol/hr/liter). GBA activities in ten adult patients with confirmed GD were less than 4.2 μmol/hr/liter and in seven infants and children with GD less than 1.24 μmol/hr/liter. This method is robust, sensitive, and suitable for high‐throughput analysis of hundreds of samples. Curr. Protoc. Hum. Genet . 82:17.15.1‐17.15.6. © 2014 by John Wiley & Sons, Inc.